Ultrasonography in Uterine Torsion: A Futuristic Tool - Sutaria , Tarun V.; Chaudhari , R.K.; Sutaria , Prajwalita (Animal Reproduction Update, 2022)
The uterine torsion is one of the commonest encountered obstetrical ailments in bovine practice, thereby impending the postpartum performance and dairy economics. The lack of accurate diagnostic procedure for the degree and duration of torsion prevents the planning of appropriate treatment protocol. Furthermore, physical examination is not adequate in uterine torsion, therefore advanced diagnostic tools like ultrasonography could be a powerful tool to assess the prognosis of the clinical case. The usage of ultrasonography helps to detect uterine adhesions, degenerative changes in uterus and fetal fluid, fetal viability, further color Doppler ultrasound helps to know the uterine vascular perfusions. The advanced image analysis yields an unbiased interpretation of the sonogram. In the future, the combination of both greyscale ultrasounds with image analysis with the support of Doppler ultrasound may be used to predict the histological changes in the uterine wall.